Manajemen Pengembangan Keprofesian Berkelanjutan (PKB) bagi Guru dan Kepala Sekolah - Mulyono, Mulyono (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The purpose of this study is to examine the management of sustainable professional development (SPD) for teachers and principals. By using library research methods and content analysis techniques, the results of this study can be concluded as follows: First, sustainable professional development management is a competency development program for teachers and principals which is implemented according to the needs, gradually, continuously to improve teacher professionalism. Secondly, teachers and principals are obliged to carry out SPD activities in stages at each level of their ranks with the aim that every teacher and headmaster can maintain, improve, and expand their knowledge and skills to carry out the learning process professionally. The big goal of the SPD activity is the realization of quality learning to improve abilities in the fields of knowledge, skills and attitudes of students. Third, the implementation of sustainable professional development management includes planning, implementing, evaluating, and reflecting activities designed to improve characteristics, knowledge, understanding, and skills. Through an evaluation cycle, reflection on learning experiences, planning and implementation of teacher professional development activities on an ongoing basis, it is hoped that teachers and principals will be able to accelerate the development of pedagogical, professional, social, and personality competencies for career advancement. Fourth, teachers and principals can implement sustainable professional development management through several programs, namely: 1) Self-development, which includes: a) following functional training; and b) carrying out teacher collective activities. 2) Scientific publications, which include: a) making scientific publications on research results; and b) make book publications. 3) Innovative works, which include: a) discovering fixed technology; b) find / create art; c) create / modify learning tools; and d) follow the development of standards, guidelines, questions and the like. Fifth, with the realization of sustainable professional development management for teachers and principals that are programmed in stages and tiered it is expected to improve: 1) the professionalism of each teacher and school principal; 2) improve the quality of learning and competence of students in the mastery of knowledge, skills and attitudes; 3) improve the quality of education nationally in order to realize the nation's competitiveness Indonesia in the global era.